Conditions: Online Professional Development in Early Childhood Education - Pölzl-Stefanec, Eva; Feierabend, Sarah (South Sulawesi Education Development, 2025)
This article examines the conditions for effective participation in online professional development (OPD) for early childhood education (ECE) professionals in Austria. Drawing on international research, it emphasizes the critical role of continuous professional development in enhancing the quality of early childhood education and care, which ultimately benefits children's long-term development. With digital formats gaining popularity due to their flexibility and accessibility, this study explores the specific needs and challenges Austrian ECE professionals face when engaging in OPD. Based on a quantitative survey of 269 ECE professionals, the study identifies five key themes: OPD attendance, preferences for OPD, general conditions for OPD, the influence of location, and time management. The results reveal a strong preference for flexible OPD formats, highlighting the value of small group sizes, German-language materials, interactive elements, and practical transfer tasks. The findings underscore the importance of a target-oriented OPD design that addresses structural barriers, including staff shortages, inadequate technical equipment, and time constraints. By providing tailored and accessible digital learning opportunities, OPD can support ECE professionals in their professionalization efforts, thereby strengthening the field of early childhood education in Austria.